LEAN MANUFACTURING AND CIRCULAR ECONOMY: relevant factors for sustainable development - Junior, Eleandro Bonini; Casagrande, Diego José (Revista Interface Tecnológica, 2025)
The world has been experiencing the need to reduce environmental impacts. Many environmental disasters have marked a society that is currently seeking to develop sustainably. Lean Manufacturing and the Circular Economy are based on responsible and economical production, considerably reducing waste, reducing waste generation and polluting less, which is in line with the Agenda 30, which aims for a more sustainable and equitable world. The objective of this study is to highlight how Lean Manufacturing and the Circular Economy are proposals for promoting sustainable development. The methodology used for this study was a Literature Review, where the Google Scholar and SciELO databases were consulted, as well as reliable websites that address the topic of this study. The studies analyzed show how Lean Manufacturing and the Circular Economy have helped companies produce more with less environmental impact, which becomes relevant, especially in light of years of negative results from environmental impacts. The world is currently seeking to prepare itself to leave future generations a healthier environment that can promote quality of life.
Keywords: Production. Economy. Waste. Cultural Change